2021
DOI: 10.1088/1757-899x/1068/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Cutting Feasibility on Ni-CBN on HSS Substrates for Aerospace Material

Abstract: The study involves coating the high-speed steel (HSS) tool with cubic Boron via electroless nickel co-deposition. The surface coating of Ni-CBN was deposited via electroless nickel where the process of involved chemical reactions as the ceramic CBN powders was embedded within the layer. By introducing the electroless nickel process, the coating cost and procedure could be simplified. The electroless deposition has been extensively practised in industry, and the most prevalent coating offers excellent corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…High-value of feed rate, spindle speed and depth of cut and cutting time will cause significant tool wear. The previous studies found that the cutting speed and feed rate interaction is significantly affecting the tool wear [52,55,56].…”
Section: Tool Wear and Tool Life Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…High-value of feed rate, spindle speed and depth of cut and cutting time will cause significant tool wear. The previous studies found that the cutting speed and feed rate interaction is significantly affecting the tool wear [52,55,56].…”
Section: Tool Wear and Tool Life Analysismentioning
confidence: 99%
“…This demonstrates spindle speed as the significant factor that affects surface roughness. Spindle speed is the most critical machining parameter affecting surface roughness because it is substantially influenced [56]. The table also represents the Taguchi response to determine the optimal factors affecting surface roughness.…”
Section: Factor Level Combination and Determination Of Optimum Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 High melting point metal nickel is a nice choice due to its excellent properties. 5,6 Electroless nickel (EN) deposition is an effective and important surface modification technology, which not only maintains the characteristics of the material itself but also endows new characteristics such as electromagnetics, [7][8][9][10][11] heat, [12][13][14] and optics. 15,16 Various metal patterns have been effectively, uniformly, and controllably grown on a matrix of various shapes and materials in the absence of an electron source, ultrahigh vacuum, high pressure, or high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the inherent brittleness and hardness of ceramic materials, YSZ materials are often mixed with others to form ceramic‐matrix materials 3,4 . High melting point metal nickel is a nice choice due to its excellent properties 5,6 . Electroless nickel (EN) deposition is an effective and important surface modification technology, which not only maintains the characteristics of the material itself but also endows new characteristics such as electromagnetics, 7–11 heat, 12–14 and optics 15,16 .…”
Section: Introductionmentioning
confidence: 99%